Formulasi Dan Potensi Ekstrak Metanol Rumput Laut Ulva lactuca Sebagai Tabir Surya - Putnarubun, Cenny; Latar, Dullah Irwan; Renggur, Mala; Resulva, Indah; Hanoatubin, Marthinus Imanuel (Jambura Fish Processing Journal, 2025)
This study aims to develop the potential of green algae (Ulva lactuca) in the local waters of the Kei islands with the best formulation and effectiveness of sunscreen obtained from ethanol extract of green algae (Ulva lactuca). Experimental research methods with methanol extraction of seaweed, sunscreen formulation and organoleptic tests and sunscreen characterization include homogeneity, pH, spreadability, and viscosity of the results obtained by organoleptic tests based on the results obtained, namely the dosage form in the form of semi-solid with a brownish color and a distinctive odor. The results of the study are the color produced by the Ulva lactuca extract cream concentration used. The higher the concentration of the extract, the greener the color of the cream. The homogeneity test of the cream in the F1, F2, F3 treatment showed a homogeneous cream seen from the even distribution of the cream, the pH test of the three extract creams F1, F2, and F3 obtained the results of a safe pH value and very feasible to use. In accordance with the pH of the skin which is 4.5 - 6.5. The results of the spreadability test showed that the F2 cream preparation met the requirements of the spreadability of the cream, while F1 and F3 were smaller than the standard spreadability of good topical preparations. The viscosity test showed that the viscosity values of F1, F2 and F3 reached 22.5 - 51.9% cp. The quality standard for sunscreen cream preparations, the viscosity of a good preparation ranges from 2000 - 50,000 cP, so it can be said that the three creams meet good viscosity standards.